2003
DOI: 10.1073/pnas.0336792100
|View full text |Cite
|
Sign up to set email alerts
|

Non-heme iron enzymes: Contrasts to heme catalysis

Abstract: Non-heme iron enzymes catalyze a wide range of O2 reactions, paralleling those of heme systems. Non-heme iron active sites are, however, much more difficult to study because they do not exhibit the intense spectral features characteristic of the porphyrin ligand. A spectroscopic methodology was developed that provides significant mechanistic insight into the reactivity of non-heme ferrous active sites. These studies reveal a general mechanistic strategy used by these enzymes and differences in substrate and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
187
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(195 citation statements)
references
References 40 publications
(31 reference statements)
8
187
0
Order By: Relevance
“…Enhancement of F4 may occur via pre-or near-resonance with its 318-nm absorption (4), whereas excitation of FX may be even less favorable implying either a larger energy difference from the electronic transition or a weaker chromophore. Although the Fe II alkoxo complex should not exhibit charge transfer transitions similar to the Fe II -αKG-TauD complex (27), the low symmetry of the Fe II site in TauD may favor spin-forbidden mid-UV transitions below 300 nm, thus allowing for a weak enhancement of oxygen vibrations. In any case, the rapid isotope-dependent disappearance of FX shows that it originates from a transient substrate-derived species.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of F4 may occur via pre-or near-resonance with its 318-nm absorption (4), whereas excitation of FX may be even less favorable implying either a larger energy difference from the electronic transition or a weaker chromophore. Although the Fe II alkoxo complex should not exhibit charge transfer transitions similar to the Fe II -αKG-TauD complex (27), the low symmetry of the Fe II site in TauD may favor spin-forbidden mid-UV transitions below 300 nm, thus allowing for a weak enhancement of oxygen vibrations. In any case, the rapid isotope-dependent disappearance of FX shows that it originates from a transient substrate-derived species.…”
Section: Discussionmentioning
confidence: 99%
“…[40] This model involves initial substrate binding that causes the conversion of the iron center from 6-to 5-coordinate. The enzyme is now ready to coordinate dioxygen and it has been suggested that this allows the enzyme to control reactivity and only implement dioxygenation when sufficient substrate is available.…”
Section: Discussionmentioning
confidence: 99%
“…68,78,[82][83][84][85][86] MCD measures the differential absorption of left and right circular polarised light, similar to circular dichroism (CD), but in the presence of a magnetic field. 84 Application of a magnetic field parallel to the direction of light causes all matter to exhibit MCD activity so it is not restricted to paramagnetic materials.…”
Section: Catalytic Mechanism Of Gpdqmentioning
confidence: 99%